A Solutions based approach to MBSE architectures with UPDM. Issue 1 (June 2013) - Hause, Matthew
Abstract: UPDM is the Unified Profile for DoDAF and MODAF. The UPDM specification was developed by a diverse group of tool vendors, end users, academia, and government representatives. UPDM enjoys the full support of the DOD and MOD and is a DoD mandated standard. The UML/SysML foundation improves the integration between architectural framework modeling and system modeling to support post acquisition life‐cycle design and implementation. This tutorial provides an overview of SysML, a brief introduction to how UPDM will provide a standard means of expressing DoDAF and MODAF using SysML and UML, an overview of the UPDM views and viewpoints and language concepts, and selected sample problems to demonstrate how the language can be used. Following this, the course will proceed to demonstrate how the MBSE foundation of UPDM can provide the answers to problems found in projects: How to avoid the problems of stovepipe development? How to ensure that systems deployment is in line with capability deployment requirements? How to effectively use MBSE to provide trade‐off analysis? How to transition from a system of systems to systems development? How to ensure system interfaces are compatible? How to communicate with non‐experts? How to reuse architectures? How to integrate requirements management into modeling? Rather than proceed in a mechanistic fashion through the different UPDM views, the course instead concentrates on the benefits of the framework using a solutions‐based approach.